The Russian Geopolitics of Energy - Vlčková, Kateřina (2015)
This Thesis is titled The Energy Geopolitics of Russia and its main purpose is to analyze the energy geopolitics of Russia and the country's shifting energeopolitical pivot to Asia, especially to China. The Thesis is divided into three respective sections -- a theoretical approach, Russian geopolitics of energy, and one descriptive and exploratory case study. It strives to answer three main research questions considering Russia's shifting energeopolitical pivot, Ukraine crisis, and the development of Russia's foreign policy in regard to her energy geopolitics.